2018
DOI: 10.14744/nci.2018.01328
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HDV Seroprevalance Among Patients with Past HBV Infection

Abstract: OBJECTIVE:This prospective study aimed to determine the prevalence of anti-HDV seropositivity among subjects who had previous hepatitis B virus (HBV) infection.METHODS:Subjects who were admitted to the gastroenterology inpatient clinic of our hospital between August 2016 and July 2017 were screened for previous HBV infection. The subjects who had HBV serology compatible with resolved HBV infection were recruited in the study, and the seroprevalance of anti-HDV was studied. Participants answered a short questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
4
1
5
Order By: Relevance
“…The HDV infection rate was reported to be as high as 14.66% among 1890 HBV patients from east and northwest of Pakistan (22). Likewise, the prevalence rates of the infection in Turkey (9.6%) and Iraq (6.6%) were higher than the prevalence reported in the present study (23,24). Furthermore, an earlier study demonstrated a significantly higher HDV seroprevalence (26.66%) among Afghans who immigrated to Iran than among Iranian patients (1.85%) (25).…”
Section: Discussioncontrasting
confidence: 61%
“…The HDV infection rate was reported to be as high as 14.66% among 1890 HBV patients from east and northwest of Pakistan (22). Likewise, the prevalence rates of the infection in Turkey (9.6%) and Iraq (6.6%) were higher than the prevalence reported in the present study (23,24). Furthermore, an earlier study demonstrated a significantly higher HDV seroprevalence (26.66%) among Afghans who immigrated to Iran than among Iranian patients (1.85%) (25).…”
Section: Discussioncontrasting
confidence: 61%
“…In recent studies, the prevalence of HDV infection in HBsAg positive patients was reported to be 9.6% in Turkey and 6.6% in Iraq. 27,28 The differences in HDV prevalence between different countries may be related to variation in the prevalence of risk factors. Like HBV, transmissions from blood products, intravenous drug users, sexual behaviors and maternal-child transmission are the most prevalent rout of transmissions for HDV.…”
Section: Discussionmentioning
confidence: 99%
“…De la même manière, Makhlouf et al (2019) ont rapporté une séroprévalence anti-VHD de 43% chez des patients hospitalisés dans une institution hospitalière d 'Egypte, alors qu'au Burkina Faso, Sawadogo et al (2016) rapportent une séroprévalence anti-VHD de 3,38% dans une population de donneurs de sang porteurs de l'AgHBs au centre régional de transfusion sanguine de Bobo-Dioulasso. D'autre part, Sahin et al (2018) ont rapporté une séroprévalence anti-VHD de 9,6% chez les sujets AgHBs positif dans une zone d'endémie en Turquie, alors que Ifeorah et al (2017) avancent une séroprévalence de 7,1% dans une étude réalisée à Abuja au Nigéria chez les personnes infectées par le VIH et vivant avec l'hépatite B.…”
Section: Discussionunclassified
“…Le virus de l'hépatite D (VHD) est un virus à ARN simple brin d'environ 1,7 kb, et est le seul membre de la famille des Deltaviridae (genre Deltavirus) (Daw et al, 2018). Le VHD nécessite les protéines de surface (AgHBs) de VHB pour constituer les particules virales infectieuses (Abdulazeez et al, 2014 ;Lozes et al, 2016 ;Sawadogo et al, 2016 ;Sahin et al, 2018 ;Makhlouf et al, 2019). Les patients présentant une infection chronique à VHB constituent le principal groupe susceptible de surinfection par le VHD, bien que les coinfections sont aussi décrites (Njemanze et al, 2009 ;Botelho-Souza et al, 2017 ;Chen et al, 2018 ;Sanou et al, 2018).…”
Section: Introductionunclassified